Fears from the age of 6 onwards (Journal of Parents and Teachers, 2026)
Fears that develop after the age of six can turn into phobias if they are not dealt with properly at home and at school. Practical guidelines are provided to help parents promote safety and open communication. This is a guide to fostering confidence and healthy child development.
Keywords: Childhood, fears, phobias, guidelines and family.